2019
DOI: 10.1017/neu.2019.2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intervention at traffic schools reducing impulsive action, and association with candidate gene variants

Abstract: ObjectiveRoad traffic injuries are the leading cause of death among young people. Recognition of the contribution of impulsive behaviour may help novice drivers to behave more safely. Previously a brief intervention focusing on impulsive traffic behaviour conducted by psychologists in driving schools had been effective. The aim of this study was an independent re-evaluation of the effect of the intervention, as conducted by driving school teachers, and assessment of the potential associations with candidate ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…In our study disinhibition in 25-year-old women was correlated with high levels of total and LDL cholesterol in 15 years old girls. The gender differences may relate to the central serotonergic function, one of the possible mediators of serum lipid levels and impulsivity (Steegmans et al, 1996;Terao et al, 2000;Vevera et al, 2003;Luht et al, 2019). Serotonin pathways function as a behavioural restraint system that inhibits impulsive behaviour (Miyazaki et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study disinhibition in 25-year-old women was correlated with high levels of total and LDL cholesterol in 15 years old girls. The gender differences may relate to the central serotonergic function, one of the possible mediators of serum lipid levels and impulsivity (Steegmans et al, 1996;Terao et al, 2000;Vevera et al, 2003;Luht et al, 2019). Serotonin pathways function as a behavioural restraint system that inhibits impulsive behaviour (Miyazaki et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…to action with less forethought than risk-free, but high Maladaptive impulsivity has high harm risk while Adaptive impulsivity supports success by agility. Previously, AMIS has been applied in a series of studies on risk-taking behaviour and impulsivity-related candidate genes studies, and found to have good predictive validity (e.g., Eensoo et al, 2004;Paaver et al, 2006;Laas et al, 2015a;Laas et al 2015b;Laas et al, 2017;Luht et al, 2019) At age 25, the Mini-International Neuropsychiatric Interview (MINI.5.0.0), (Sheehan et al, 1998) Estonian version (Shlik et al, 1999) Likert scale questions about misprize within the family and about emotional and physical abuse (Paaver et al, 2008;Kiive et al, 2010).…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Being a 9R carrier has been associated with persistent ADHD in adults (Franke et al, 2012(Franke et al, , 2010. This genotype can also be associated with traffic risks: We have previously found that male 9R carriers had more accidents in traffic by their own fault (Tokko et al, 2019) and, in another sample, a higher general traffic risk (Luht et al, 2019).…”
Section: Introductionmentioning
confidence: 93%
“…Because AMIS combines items from the original Dickman’s impulsivity scale with NEO-PI-R items, the 2 primary dimensions of the questionnaire were named adaptive and maladaptive impulsivity to avoid confusion. Previously, AMIS scores were used to investigate driving and substance abuse: adaptive and maladaptive impulsivity scores were associated with risky driving and alcohol abuse in nationally representative samples of car drivers ( Eensoo et al, 2004 ; Paaver et al, 2006 ; Luht et al, 2019 ) and in a cross-sectional analysis on the ECPBHS ( Laas et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%